Wound Response in Teak Trees from Western Ghats of India and its Potential in Dendroecology - Sinha, Satish Kumar; Deepak, M. S.; Vijendra Rao, R. (Indian Forester, 2010)
Investigations on tree ring analysis in Tectona grandis Linn (teak) from Western Ghats showed the presence of crescent, elongate and triangular-shaped scars as evidence of wounds due to insect, fire damage and nail penetration. Insect wounds remained open and restoration of disrupted cambium took five to six years. In cross section, most discs displayed little callus tissue. Fire scars were identified by the presence of charcoal around the scars and elongated scars were due to nail penetration. Each of these are potential sources to establish a relationship with dendroecology.